2020
DOI: 10.1210/clinem/dgaa658
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association for HbA1c in Malay Identified Deletion on SLC4A1 that Influences HbA1c Independent of Glycemia

Abstract: Context Glycated hemoglobin A1c (HbA1c) level is used to screen and diagnose diabetes. Genetic determinants of HbA1c can vary across populations and many of the genetic variants influencing HbA1c level were specific to populations. Objective To discover genetic variants associated with HbA1c level in nondiabetic Malay individuals. Design and Participants We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…GWAS performed as a part of the Singapore Malay Eye Study and Living Biobank study indicated deletions at SLC4A1 (rs769664228) are associated with reduced HbA1c levels. This variant has been significantly associated with the Malay population (Chai et al, 2020). Metabolic syndrome is one of the risk factors for T2D.…”
Section: Inter-ethnic Genetic Variations In Genes Regulating Amino Ac...mentioning
confidence: 94%
“…GWAS performed as a part of the Singapore Malay Eye Study and Living Biobank study indicated deletions at SLC4A1 (rs769664228) are associated with reduced HbA1c levels. This variant has been significantly associated with the Malay population (Chai et al, 2020). Metabolic syndrome is one of the risk factors for T2D.…”
Section: Inter-ethnic Genetic Variations In Genes Regulating Amino Ac...mentioning
confidence: 94%
“…Discuss both direction and magnitude of any potential bias and any efforts to address them 11 Our findings may not apply to other ethnic groups given that we used populations with European ancestry only. This may especially be a concern in populations with higher prevalence of hemoglobinopathies and red cell disorders (38)(39)(40)(41)(42). Additionally, analyses were not stratified by sex, which is a major determinant of body composition and IR/HI (34).…”
Section: Limitationsmentioning
confidence: 99%
“…Whilst this may appear more tractable for pharmacogenomic phenotypes, given their relatively simpler genetic architectures, the key hurdles of human genomics research remain particularly in moving from genetic association to biological understanding, supporting the need for functional genomic and biological experimental follow up (Figure 3). A recent cautionary example from the analysis of a diabetes biomarker shows how a putatively causal variant in a membrane transporter ended up being a confounded signal from an unrelated population-specific blood trait (Chai et al, 2020). Without similar and careful evaluations, genomic studies are vulnerable to attempting to derive causal mechanisms from incomplete information on gene function, tempted by the "narrative potential" of the human genome (Goldstein et al, 2013).…”
Section: Pharmacogenomic Phenotypes: Simple Trait Genomics?mentioning
confidence: 99%